I'm No Princess: Super Hero Girls Together. Issue 1 (1st March 2019) - Baker, Lucy I.
Abstract : DC Super Hero Girls (DCSHG) is a trans-media franchise that includes not just screen media texts but a wide array of themed merchandise aimed at a multi-generational market. I argue here that key components of the franchise present a queered version of girlhood that critiques femininity as a gender role while presenting femaleness as encompassing a variety of signifiers, acts, and presentations that can be read as queer (particularly by the so-called big girls in the audience). This is evident in the representation of queer relationships that exist in the sexualized zone of the canonical material, allowing the DCSHG characters to inhabit a liminal proto-queer space between homosocial/gender non-conforming and lesbian that is considered more appropriate for young girls. I examine the way in which the DC Super Hero Girls franchise rejects and reforms familiar elements of comics, super heroism, and princess culture to create that space for girls.